Hubungan Antara Lama Sakit dengan Kualitas Hidup Anak Penderita DMT1 Saat Pandemi Covid-19 di RSUD Soetomo Surabaya - Kevin Almas Maromi; Nur Rochmah; Bambang Hermanto (Universitas Batanghari Jambi, 2021)
This study aims to determine the relationship between length of illness and quality of life of people with Type 1 Diabetes Mellitus during the COVID-19 pandemic. This research is an analytical description study with a cross-sectional research approach using a questionnaire with telephone interview techniques. The questionnaire in this study was based on several guidelines and previous research. Measurements using PedsQl 3.2 Diabetes Module. Data were collected using a validated questionnaire consisting of 33 question items. The data was collected during October 2020. A total of 33 questionnaires were successfully distributed to patients at the Children's Clinic of Dr. RSUD Dr. Soetomo Surabaya who participated in this research. The data were then analyzed by non-parametric test using the Spearman correlation test method using IBM SPSS Statistics 25. Based on the quality of life assessment using the PedsQL questionnaire, 17 respondents (51.6%) had a near-poor quality of life, and 16 respondents had a near-good quality of life. The most disturbed domain is related to worry, which is as many as 20 respondents (60.7%). Meanwhile, the proportion of respondents with the highest quality approaching good was found in treatment I as many as 19 respondents (57.6%). There was also a positive and significant correlation between related to the disease, P Value 0.007 < 0.05, related to treatment I, P Value 0.011 <0.05, related to anxiety, P value 0.009 < 0.05, and related to communication, P Value of 0.016 < 0.05. In addition, there was also a significant negative relationship with regard to treatment II, P Value 0.000 < 0.05.